Eliminating the Darkness of Ignorance: Understanding the Importance of Literacy in Islam - Kultsum, Umu (Walidem Institute and Publishing (WIP), 2024)
This research aims to explore and understand the role and importance of literacy in the context of Islamic teachings, as an effort to eliminate ignorance and increase awareness and understanding of mankind. Using a qualitative approach and textual analysis of primary and secondary sources, this study explores how Islam emphasized the importance of knowledge and literacy from the beginning of revelation, as well as its implications for the development of a civilized and knowledgeable society. The results of the study show that literacy, in the context of Islam, is not only limited to the ability to read and write, but also includes the ability to understand, analyze, and apply knowledge in daily life. The teachings of Islam, which commands its people to 'Iqra' or 'read' in the first revelation to the Prophet Muhammad (PBUH), affirm the urgency of literacy as the key to opening the door to wisdom and enlightenment. Furthermore, the study identifies various aspects of literacy emphasized in Islam, including religious literacy, scientific literacy, and social literacy, all of which contribute to the formation of individual character and the advancement of society. This study concludes that a deep understanding of the importance of literacy in Islam can be a foundation for overcoming the challenges of ignorance and encouraging holistic human resource development. Thus, efforts to improve literacy are not only limited to individual responsibility but also part of the collective obligation of Muslims to build a knowledgeable and dignified civilization.